The Impact of Homecare on Breastfeeding Skills in Postpartum Mothers - Sri Anggarini Parwatiningsih; M. Nur Dewi Kartikasari; Septiana Juwita (JURNAL INFO KESEHATAN, 2025)
The postpartum period is a critical phase for both mothers and newborns, during which the mother's physical and psychological recovery occurs alongside the initiation of breastfeeding. Although breastfeeding is a natural process, many postpartum mothers face challenges in initiating and sustaining effective breastfeeding practices. Homecare has emerged as an effective strategy to improve maternal and child health. This study aims to analyze the impact of homecare on breastfeeding skills in postpartum mothers. The study was conducted in Surakarta City used a quasi-experimental design with a pretest-posttest with control group approach. Purposive sampling was employed, involving a total of 50 respondents divided equally into two groups: an intervention group and a control group. A 30-day breastfeeding skills training intervention was provided to postpartum mothers, carried out by midwives, with each session lasting 30 minutes per day. Data analysis was conducted used the paired t-test the Wilcoxon signed- rank test. Results showed that the paired t-test of the control group pretest and posttest with a mean value of 0.52 and the paired t-test of the intervention group pretest and posttest with a mean value of 5.44. While the statistical significance showed the p-value for the control group was 0.0018 and for the intervention group was approximately 0.0000000596. These findings demonstrate strong statistical significance, supporting the hypothesis that homecare exert a positive effect. In conclusion, homecare play a significant role in enhancing breastfeeding skills among postpartum mothers, with greater improvements observed in the intervention group compared to the control group.